2014
DOI: 10.1007/s12471-014-0577-1
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of LV ejection fraction using real-time 3D echocardiography in daily practice: direct comparison of the volumetric and speckle tracking methodologies to CMR

Abstract: AimsThis study is the first to directly compare two widely used real-time 3D echocardiography (RT3DE) methods of cardiac magnetic resonance imaging (CMR) and assess their reproducibility in experienced and less experienced observers.MethodsConsecutive patients planned for CMR underwent RT3DE within 8 h of CMR with Philips (volumetric method) and Toshiba Artida (speckle tracking method). Left ventricular ejection fraction (LVEF), left ventricular end-diastolic volume (LVEDV) and end-systolic volume (LVESV) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 22 publications
2
26
0
1
Order By: Relevance
“…Therefore, both 3DSTE and CMR are clinically applicable for measuring LV volumes but cannot be used interchangeably as is the case for most cardiac imaging modalities. The obtained good correlation and accuracy for LVEF between 3DSTE and CMR has been previously reported [ 7 ] and its accuracy and reproducibility was not affected by observer experience compared with the volumetric method [ 13 ]. This finding has important clinical consequences as LVEF is the most frequently performed echocardiographic assessment and many clinical decisions depend on its accurate measurement such as when to initiate cardiac medications, guide device therapy or perform cardiac surgery.…”
Section: Discussionsupporting
confidence: 71%
“…Therefore, both 3DSTE and CMR are clinically applicable for measuring LV volumes but cannot be used interchangeably as is the case for most cardiac imaging modalities. The obtained good correlation and accuracy for LVEF between 3DSTE and CMR has been previously reported [ 7 ] and its accuracy and reproducibility was not affected by observer experience compared with the volumetric method [ 13 ]. This finding has important clinical consequences as LVEF is the most frequently performed echocardiographic assessment and many clinical decisions depend on its accurate measurement such as when to initiate cardiac medications, guide device therapy or perform cardiac surgery.…”
Section: Discussionsupporting
confidence: 71%
“… 3DSTE has a lower frame rate and spatial resolution compared to its 2D counterpart. As the full 3D dataset is the result of combining 6 wedge‐shaped subvolumes, there could be so‐called “stitching noise” on each border rendering the dataset useless. 3D echocardiographic systems have a tendency to underestimate LV volumetric parameters; most affected is LV‐EDV, thus resulting in a seemingly lower LV‐EF as compared to conventional 2D echocardiographic results In the present paper, other chambers than the LV were not examined. Further imaging or other diagnostic techniques were not performed to rule out any hidden subclinical pathologies in cases with LV‐RBR. Analyzing 3DSTE‐derived LV strain parameters was not the goal of the present study either. …”
Section: Discussionmentioning
confidence: 96%
“…• 3D echocardiographic systems have a tendency to underestimate LV volumetric parameters; most affected is LV-EDV, thus resulting in a seemingly lower LV-EF as compared to conventional 2D echocardiographic results. 36 • In the present paper, other chambers than the LV were not examined.…”
Section: Limitation Sectionmentioning
confidence: 94%
“…Volumes derived with echo are underestimated compared with ‘gold standard’ magnetic resonance imaging (MRI) [ 14 , 15 ]. Nevertheless a meta-analysis found a mean difference between the two modalities of close to 0 %, although a large spread and heterogeneity between studies was observed [ 8 ].…”
Section: Patient Selectionmentioning
confidence: 99%
“…Echocardiography could play a larger role in CRT, especially if 3D acquisition were to become more feasible for clinical practice. Increased spatial and temporal resolution could make 3DE applicable for fast acquisition of volumetric status and myocardial strain [ 14 , 39 ]. A single acquisition could therefore incorporate information on function, volume, viability, dyssynchrony, and options for LV lead positioning.…”
Section: Future Directionsmentioning
confidence: 99%